2008
DOI: 10.1016/j.jfludis.2008.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Non-linguistic auditory processing in stuttering: Evidence from behavior and event-related brain potentials

Abstract: Auditory processing deficits have been hypothesized to play a role in the disorder of stuttering (Bloodstien, 1995). The current study focused on non-linguistic auditory processing without verbal responses to rule out effects of language processing differences and articulatory planning for speaking. A pure-tone, oddball paradigm was utilized to compare behavioral responses of accuracy and reaction time, and event-related potentials elicited by brief standard and target tones. Results revealed that, as a group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 29 publications
8
50
0
2
Order By: Relevance
“…These alterations are characterized as a differential in the comparison between individuals who stutter and non-stutters, and the chance of adult individuals who stutter present this disorder is approximately 60.7 times that of non-stutters. This result was expected, considering that national and international studies have reported auditory processing difficulties in children and adults who stutter (3,(13)(14)(15)(16) . Such changes in auditory processing result in decreased ability to produce auditory perception patterns in individuals who stutter.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…These alterations are characterized as a differential in the comparison between individuals who stutter and non-stutters, and the chance of adult individuals who stutter present this disorder is approximately 60.7 times that of non-stutters. This result was expected, considering that national and international studies have reported auditory processing difficulties in children and adults who stutter (3,(13)(14)(15)(16) . Such changes in auditory processing result in decreased ability to produce auditory perception patterns in individuals who stutter.…”
Section: Discussionsupporting
confidence: 55%
“…Disabilities of auditory nature are manifested in a variety of ways. Some studies have shown evidence of decreased activity in the left auditory cortex prior to speech-language therapy and normal or improved activity levels immediately after therapy (3) . Other studies have indicated neuroanatomical differences between individuals who stutter and non-stutterers (18,19) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delayed auditory feedback in individuals who stutter decreases or inhibits stuttering (11) , and this effect is not related to the reduction of speech rate, but mainly to altered auditory input (12,13) . This fact suggests that auditory input processing could be different in individuals who stutter when compared to fluent individuals (14,15) .…”
Section: Introductionmentioning
confidence: 99%